2003
DOI: 10.1046/j.1365-2036.2003.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile composition in inflammatory bowel disease: ileal disease and colectomy, but not colitis, induce lithogenic bile

Abstract: SUMMARYBackground: Inflammatory bowel disease is a risk factor for gall-bladder stones, but there is controversy about the composition of these stones and whether such patients develop lithogenic bile. Methods: In 54 gallstone-free inflammatory bowel disease patients and 13 non-inflammatory bowel disease patients with cholesterol-rich gallstones, we measured the biliary cholesterol saturation indices, nucleation times and bilirubin concentrations, and determined the bile acid composition and molecular species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 63 publications
2
20
0
5
Order By: Relevance
“…On average, there was a 14% decrease at pH 6.2, but a 60% decrease at pH 5.75, compared with pH 6.7. Tolerance of bile salts, whose concentrations have been reported to increase in certain gut disorders (24,35), is also considered to be an important factor for survival in the intestine. Bile salt tolerance differed among isolates, particularly at the lowest concentration tested (0.1%), but all the strains tested were bile salt sensitive, showing on average 76%, 95%, and 97% inhibition at 0.1%, 0.25%, and 0.5% bile salts, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On average, there was a 14% decrease at pH 6.2, but a 60% decrease at pH 5.75, compared with pH 6.7. Tolerance of bile salts, whose concentrations have been reported to increase in certain gut disorders (24,35), is also considered to be an important factor for survival in the intestine. Bile salt tolerance differed among isolates, particularly at the lowest concentration tested (0.1%), but all the strains tested were bile salt sensitive, showing on average 76%, 95%, and 97% inhibition at 0.1%, 0.25%, and 0.5% bile salts, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These differences in the presence or absence of a specific phylotype can be explained by different abilities to adapt to a diseased gut environment or mucosal status. For instance, it has been reported that CD patients often have acidic stools with elevated bile salt concentrations (57,58), and other factors, such as oxidative stress or thiol availability, are also likely to lead to a significantly altered microbiota (59,60). Supporting this hypothesis, F. prausnitzii representatives are sensitive to changes in the gut physicochemical conditions that may occur during disease, such as a pH reduction or a change in the bile salt content (35), and are extremely sensitive to oxygen, although they can persist in environments with oxygen due to a flavin-thiol-dependent extracellular electron shuttle (61).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jung et al [18] have demonstrated that ASBT is apparently downregulated in Crohn’s disease, which is consistent with a decreased bile acid absorption in ileitis [19, 20]. Probably due to increased bile acid loss, patients with resected or non-resected Crohn’s disease frequently suffer from gallstones either of the cholesterol or the pigment type [21,22,23,24]. The proinflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin (IL)-1β are known to regulate organic anion transporters which are involved in the enterohepatic circulation, including ASBT [25].…”
Section: Introductionmentioning
confidence: 93%